Biomarkers of vitamin D status in healthy adults: associations with serum lipid parameters – a pilot study - Zeljković, Aleksandra; Vladimirov, Sandra; Gojković, Tamara; Vekić, Jelena; Mihajlović, Marija; Spasojević-Kalimanovska, Vesna (Archives of Pharmacy, 2022)
Vitamin D deficiency is among important healthcare challenges today. Traditionally, vitamin D status is assessed through determination of 25-hydroxy metabolite (25(OH)D), but novel data point to 24,25(OH)2D and 25(OH)D/24,25(OH)2D ratio (VDMR) as promising biomarkers. It is widely accepted that the biological role of vitamin D exceeds its well-known contribution to bone turnover. However, its effects on overall energy metabolism and lipid status alterations are not completely understood. In this study, we analyzed the relationship of vitamin D status assessed as concentrations of 25(OH)D3 and 24,25(OH)2D3 determined by liquid chromatography-tandem mass spectrometry, as well as VDMR with advanced lipid status parameters. Vitamin D status biomarkers, routine parameters of lipid status and size and distribution of lipoprotein subclasses were determined in 89 healthy adults (35 with adequate vitamin D status and 54 with vitamin D deficiency). Our results indicated a preponderance of pro-atherogenic small, dense LDL particles (sdLDL) in vitamin D deficient subjects. Both 25(OH)D and 24,25(OH)2D were associated with a relative proportion of sdLDL (β: -0.410; SE: 0.154; P=0.010; and β: -2.041; SE: 0.969; P=0.039, respectively). Positive correlation was found for VDMR and relative proportion of HDL 3a particles (ρ=0.251; P=0.024). VDMR value was decreased in subjects with vitamin D deficiency (P=0.001), thus implying its usefulness as a biomarker. A thorough investigation of novel vitamin D biomarkers and advanced lipid status parameters can be useful in the estimation of individual risk for the development of cardiometabolic alterations.